Crispin the end of time - Avi 1937- (Balzer + Bray, 2010)
As Crispin tries to fulfill Bear's dream of moving to Iceland, he must leave Troth behind at a convent that needs a healer but, after falling in with thieves posing as musicians, he makes a new friend, Owen, and together they continue the arduous journey.